Leading local government : the role of directly elected mayors - Fenwick, John; Johnston, Lorraine (Bingley, U.K. : Emerald Publishing Limited, 2020)
Leading Local Government: The Role of Directly Elected Mayors is a timely and critical book that examines the erratic rise and uncertain future of the directly elected mayor in the context of English local governance. Written principally for local government practitioners as well as for those with an academic interest in public leadership, the book asks whether elected mayors offer a new and reinvigorated form of local leadership, whether for individual towns and cities or for wider groups of combined authorities at the regional level. Built on original primary research conducted with mayors, elected representatives and a range of public sector managers, the book offers a fresh perspective that recognises mayoral achievements in some areas - including economic development - but finds that mayors do not enjoy widespread public endorsement and do not represent devolution of power in any meaningful sense. Above all, the book argues that elected mayors do not represent democratic renewal in a country which remains highly centralized. Using an historical account of early local government leaders together with international comparisons from the United States and Europe, the authors present the argument that, twenty years into the mayoral experiment, the mayoral initiative has so far failed to match the aspirations of central government for a new and effective form of local leadership.
Chapter 1. Introduction and scope of the book -- Chapter 2. Local administration or local leadership? A brief history -- Chapter 3. Leaders before their time -- Chapter 4. Elected mayors as local leaders? -- Chapter 5. Leading economic growth -- Chapter 6. Leaders, regions and places -- Chapter 7. The role of elected mayors: Findings and analysis -- Chapter 8. Conclusion.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Mayors -- Great Britain -- Powers and duties; Mayors -- Great Britain -- Election; Political Science -- Political Process -- General; Regional government